(untitled) (Colombia Medica, 2013)
Objective: to observe the relationship between socioeconomic status, height and nutritional problems related to obesity, overweight and risk of metabolic complications in men and women of Medellin (Colombia). Methods: cross-sectional study with a sample of 5,556 adults between 18 and 69 years of age. We assessed weight, height and waist circumference. Socioeconomic variables were evaluated by family income, socioeconomic stratum and academic level achieved. Results: we found that in men and women the height reached in adulthood is associated with socioeconomic conditions as measured by the socioeconomic strata and family income. In women, height, age, and socioeconomic strata are associated with obesity, overweight and risk of obesity, and risk of metabolic complications. Conclusion: These results are not only from individual unhealthy habits, such as eating patterns based on high density foods combined with low energy expenditure, but also from the cumulative effect of food deprivation throughout life. Therefore, policies intended to prevent them should take a preventive approach that begins before birth and continues during childhood and adulthood.